2008
DOI: 10.1152/ajprenal.00013.2007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LOX-1 therapy in rats with diabetes and dyslipidemia: ablation of renal vascular and epithelial manifestations

Abstract: LOX-1 is a multifunctional membrane receptor that binds and internalizes oxidized LDL (oxLDL). We tested the hypothesis that blockade of LOX-1 with an anti-LOX-1 antibody limits nephropathy in male rats with diabetes and dyslipidemia (ZS rats; F(1) hybrid product of Zucker fatty diabetic rats and spontaneous hypertensive heart failure rats). Lean ZS rats were controls, while untreated obese ZS (OM), ZS obese rats injected with nonspecific rabbit IgG (OM-IgG; 2 microg intravenous injection given weekly), and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 52 publications
(79 reference statements)
2
42
0
1
Order By: Relevance
“…ICAM-1 is a cell-surface protein typically stimulated by cytokines, cell stress, and oxidants (20,25). Dominguez et al showed that the levels of ICAM-1 which participate in leukocyte migration and epithelial dedifferentiation, were also found to be up-regulated in the tubules of diabetic obese rats and that this alteration was associated with LOX-1 expression induction (4). In the present study, the transfection with LOX-1 siRNA was able to attenuate both the Ang II-induced ICAM-1 expression and the adhesion between the monocytes and the HRPTEpiCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAM-1 is a cell-surface protein typically stimulated by cytokines, cell stress, and oxidants (20,25). Dominguez et al showed that the levels of ICAM-1 which participate in leukocyte migration and epithelial dedifferentiation, were also found to be up-regulated in the tubules of diabetic obese rats and that this alteration was associated with LOX-1 expression induction (4). In the present study, the transfection with LOX-1 siRNA was able to attenuate both the Ang II-induced ICAM-1 expression and the adhesion between the monocytes and the HRPTEpiCs.…”
Section: Discussionmentioning
confidence: 99%
“…Dominguez et al have shown that obese rats, a model of metabolic syndrome in which hypertension is the dominant feature, present with renal enlargement, intense oxidative stress, lipid accumulation, leukocyte infiltration, as well as renal dysfunction and fibrosis. These rats also showed LOX-1 overexpression, and treatment with anti-LOX-1 antibody significantly limited or prevented the detrimental effects of obesity on renal function (4). In vitro, the exposure of normal rat proximal tubules to oxidized LDL (oxLDL) has been shown to markedly increase levels of LOX-1.…”
Section: Introductionmentioning
confidence: 99%
“…52 The anti-LOX-1 antibody injection reduced renal inflammation and fibrosis in ZS rats. 53 Kidneys from ZS rats treated with anti-LOX-1 antibody lacked neutrophil infiltration, whereas kidneys from untreated and normal IgG-injected ZS rats had abundant clusters of neutrophils along the capillary lumens. Although anti-LOX-1 antibody did not prevent albuminuria, it increased glomerular vascular endothelial growth factor levels to help preserve renal microvascular beds.…”
Section: Lox-1 and Kidney Injurymentioning
confidence: 97%
“…Although anti-LOX-1 antibody did not prevent albuminuria, it increased glomerular vascular endothelial growth factor levels to help preserve renal microvascular beds. 53 It was also shown that the expression of the AT1 receptor in LOX-1 KO mice was lower than wild-type mice both before and after infusion of angiotensin II (Ang II). 54 Furthermore, Ang II-induced, but not norepinephrine-induced, blood pressure increase and renal injury were attenuated in LOX-1 KO mice compared with wild-type mice.…”
Section: Lox-1 and Kidney Injurymentioning
confidence: 99%
“…oxLDL binding to LOX-1 will induce apoptosis as well as expression of adhesion molecules and MMP and activate the inflammatory pathway, all of which eventually contribute to the rupture of the plaques. [45][46][47][48] In view of high expression of LOX on more than one kind of cells concerned in AS, LOX-1 will have great potential to be a target for molecular imaging of AS plaques. At present, imaging probes targeted at LOX-1 have been developed to improve sensitivity, specificity, and biocompatibility compared to the nontargeted ones.…”
mentioning
confidence: 99%